2020
DOI: 10.1103/physrevd.101.034033
|View full text |Cite
|
Sign up to set email alerts
|

Dalitz-plot decomposition for three-body decays

Abstract: We present a general formalism to write the decay amplitude for multibody reactions with explicit separation of the rotational degrees of freedom, which are well controlled by the spin of the decay particle, and dynamic functions on the subchannel invariant masses, which require modeling. Using the three-particle kinematics we demonstrate the proposed factorization, named the Dalitz-plot decomposition. The Wigner rotations, that are subtle factors needed by the isobar modeling in the helicity framework, are si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…There is a recent interest in this, motivated by the fact that the practical implementation of such rotations is highly nontrivial [29,30]. A proposal to write the 1 → 3 reaction as a sum over subchannels in the same reaction plane, and then rotate the whole sum together, was given in [31], and is referred to as "Dalitz plot decomposition". In this way, the dependence of the Wigner rotations on the relevant Mandelstam variables is apparent.…”
Section: The S-matrix and Amplitude Parameterizationsmentioning
confidence: 99%
“…There is a recent interest in this, motivated by the fact that the practical implementation of such rotations is highly nontrivial [29,30]. A proposal to write the 1 → 3 reaction as a sum over subchannels in the same reaction plane, and then rotate the whole sum together, was given in [31], and is referred to as "Dalitz plot decomposition". In this way, the dependence of the Wigner rotations on the relevant Mandelstam variables is apparent.…”
Section: The S-matrix and Amplitude Parameterizationsmentioning
confidence: 99%
“…First, we introduce the description of the three-body phase space and the Dalitz plot decomposition [26], Section 5.1, which allows to separate invariant mass and decay orientation degrees of freedom in the decay amplitude. In Section 5.2, we perform a general study of the Λ + c ⟶ pK − π + polarised decay rate, while in Section 5.3, we write the complete Λ + c ⟶ pK − π + decay amplitude written in the helicity formalism following the method of Ref.…”
Section: Three-body Decay Via Multiple Intermediatementioning
confidence: 99%
“…To simplify the Λ + c ⟶ pK − π + amplitude model expression, it is useful to separate invariant mass and decay orientation degrees of freedom applying the Dalitz plot decomposition proposed in Ref. [26]. Moreover, the properties following from rotational invariance described in Section 2.2 are enforced by construction.…”
Section: Three-body Decay Via Multiple Intermediatementioning
confidence: 99%
“…The technical aspects of this transformation and the inclusion of the dynamical part are discussed in appendix B; for completeness, a comprehensive review on Dalitz plot decomposition can be found in ref. [11]. The final amplitude for a decay A → (B → DE)C with defined helicities of all particles is…”
Section: Including Dynamicsmentioning
confidence: 99%